БОШЛАНҒИЧ СИНФ ЎҚУВЧИЛАРИНИНГ ЖИСМОНИЙ ВА ФИЗИОЛОГИК ХУСУСИЯТЛАРИ - Юсупова, З.Ш. (SCIENCE and SOCIETY, 2021)
The article scientifically examines the physical and physiological characteristics of primary school students. The importance of determining physical loads by determining the level of physical and physiological development of primary school students was noted.
Keywords: primary class; student; physical culture; physiological characteristics; movement; organism